Studi Profil Pemecahan Masalah Guru Matematika dalam Penyelesaian Soal Cerita Berbasis Strategi Heuristik Polya - Agusfianuddin, Agusfianuddin; Muzaki, Ahmad; Sabrun, Sabrun (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
Problem solving in word problems is one of the important competencies in mathematics learning that requires the ability to think critically, logically, creatively, and reflectively. This study aims to describe the profile of mathematics teachers' problem-solving abilities in solving word problems based on Polya heuristic strategies. The type of research used is qualitative descriptive with a case study design. The research subjects consisted of 16 mathematics teachers from State Junior High Schools in West Lombok Regency who were selected using purposive sampling techniques. Data collection was carried out through triangulation of sources using tests, interviews, and questionnaires. The data were analyzed in a qualitative descriptive manner to illustrate the level of application of the Polya heuristic strategy. The results showed that teachers who applied the Polya heuristic stages were complete by 20%, 30% were incomplete, 45% were incomplete, and 5% were incomplete. The low implementation of this strategy is due to the limitations of professional training, the lack of application of heuristic strategies in learning activities, and the low level of thinking skills (Higher Order Thinking Skills or HOTS). In general, teachers' ability to apply Polya heuristic strategies still needs to be improved through training and habituation of problem-solving-based learning.